« Une constellation dans la nuit de l'histoire, une tache lumineuse devant les ténèbres de la mort » : l'œuvre d'Ernst Wilhelm Nay vue par Werner Haftmann - Vincenza Benedettino (Les Cahiers de l'École du Louvre)
The professional and amicable relationship between the art historian Werner Haftmann (1912-1999) and the abstract artist Ernst Wilhelm Nay (1902-1969) in the Federal Republic of Germany during the post-war period is an emblematic case of the development of an art historiography. Through the analysis of correspondence, the modern art encyclopedia Malerei im 20. Jahrhundert, published by Haftmann in 1954, and exhibitions catalogues, this study retraces the fundamental stages of the path to the consecration of Nay’s abstract painting undertaken by the art historian in Germany and internationally. On the one hand, Nay benefited considerably from the critical support of one of West Germany’s most influential art historians. On the other hand, Haftmann forged around the work and the figure of the painter the exemplary demonstration of his theories proclaiming the triumph of abstract art respectively as the art of the future western democratic post-war world as well as a free and independent creative performance.